Corporate social responsibility disclosure in Malaysian government-linked companies / Elinda Esa and Abdul Rahman Zahari - Esa, Elinda; Zahari, Abdul Rahman (2012)
This paper mainly investigates corporate social responsibility (CSR) disclosure in the corporate annual reports of Malaysian GLCs. Although a number of studies have looked into CSR in Malaysian companies, very little or limited research has been done on GLCs. CSR can be defined as a subject that covers from business ethics, good governance and legal practices to social obligation and sustainable environment. Being a business where the government has a major ownership and control, GLCs can be expected to lead others in good governance practices including CSR practice. That is because the objective of GLCs’ formation is not purely profit driven but includes social aspects to ensure a more equitable society. The Malaysian government has promoted CSR through the introduction of the Caring Society Policy, Vision 2020, the Ninth Malaysia Plan, and the GLC Transformation program. Through the GLC Transformation program, the Silver Book was launched in September 2006. This Silver Book provides a guideline on how GLCs can proactively contribute to the society and at the same time still creates value to their shareholders. This study examines the CSR items most disclosed and examine if there has been a change in the CSR items most disclosed after the introduction of the Silver Book. The two years were chosen to see if introduction of the Silver Book in 2006 has an impact on CSR disclosure. A CSR disclosure checklist was used to score the items in the annual reports. The paired sample t test and Wilcoxon Signed-Ranks test showed that there has been a change in the most items disclosed after introduction of the Silver Book and the difference was statistically significant at 5% level. This result appears to suggest that the introduction of the Silver Book in 2006 has had a positive impact on CSR in Malaysian GLCs.